Displaced women and sexual and reproductive health services: exploring challenges women with sexual and reproductive health face in displaced camps of Nigeria. (2023)
Background: Displaced women are affected by sexual and reproductive health (SRH) challenges, often exacerbated by poor living conditions, limited access to healthcare, and cultural norms. The aim of this study was to explore SRH issues, the effects of displacement into camps on women’s SRH, and challenges with accessing and utilizing SRH services among women in camps for the displaced in Benue State, Nigeria. Methods: A qualitative phenomenological approach was employed to gain an in-depth understanding of the women’s SRH challenges, based on 12 focus group discussions between women of different age groups and eight in-depth interviews. The data were collected using tape recorders and notes. Data analysis followed a thematic approach. Ethical approval and appropriate consent were obtained for the study. Results: The majority of research participants stated that sexually transmitted disease/human immunodeficiency virus was the most serious SRH issue in the camp. Their stay in camp enhanced the women’s vulnerability and exposed them to sex in exchange for basic needs/palliatives, increasing their SRH challenges. Access to and use of SRH services were impacted by their migratory lifestyle, cultural and religious views, lack of SRH knowledge, and other difficulties. Short-term approaches to intervention, health providers’ poor communication, and attitudes were reported to affect SRH service use. Conclusion: There is an urgent need for comprehensive interventions to address SRH challenges among women in displaced settings, including proper coordination of humanitarian services, education on transactional sex, encouragement of men to participate in SRH initiatives, and expansion of access to services, as well as the training and hiring of culturally competent healthcare providers.